Paying for the War: Macroeconomic Stabilization in Poor Countries under Conflict Conditions. - FitzGerald, E (1997)
Much of the human cost in developing countries is the result of economic collapse rather than military casualties as such. This article examines the way in which the extreme macroeconomic disequilibria that almost inevitably occur in wartime are generated and what their consequences are for production, distribution and welfare. The problem is often exacerbated by misguided policies on the part of both national governments and aid agencies, based on concepts of structural adjustment and humanitarian relief designed for use in peacetime. In contrast, it is argued that a stabilization programme that explicitly takes into account changes in the behaviour of households and firms under conditions of fiscal stress, foreign exchange shortages and increased uncertainty might not only sustain essential economic activity but also protect more vulnerable groups from unnecessary hardship.